Whole genome studies of origin, selection and adaptation of the Russian cattle breeds - N. S. Yudin; D. M. Larkin (Вавиловский журнал генетики и селекции)
Our review presents several recent studies on the genetic history and signatures of selection in genomes of the native Russian cattle breeds. Most of these works are not easily accessible for the Russian-speaking audience. We describe the origins of appearance of the Russian cattle breeds from the genetics perspective. We point to the links between most of the Russian breeds with the taurine breeds of the European origin and for some Russian breeds with the breeds of the Asian origin. We describe major phylogenetic clusters of the Russian breeds and point to those that still maintain their unique genetics, meaning that their preservation is a priority. In addition, we review the results of the search for signatures of selection in genomes of the Russian cattle breeds. Some unique signatures of selection present in the genomes of so-called “turano-mongolian” cattle (i. e. the Yakut cattle) are described which allowed the Yakut cattle to adapt to harsh environments found above the Polar Circle. Signatures of selection which could help other cattle breeds of the Russian origin to adapt to various climatic condition of the Russian Federation are reviewed. The Russian cattle genomes also contain known signatures of selection related to cattle domestication about 8–10 thousand years ago. The most profound ones include genes related to changes of the coat colour. This phenotype in many cases could be related to the distinction of the first domesticated populations and lead to the formation of so-called land races (primitive breeds). Whole-genome association studies of Russian cattle breeds pointed to a novel gene which could be related to the “white-faced” phenotype and to a gene which is related to body temperature support under the acute cold stress. The data presented in our review could be used for identification of genetic markers to focus on in future efforts on designing new highly productive cattle breeds adapted to climates of the Russian Federation and other countries with similar climates.